AJARAN SAMNYASA DALAM MANAWA DHARMASASTRA - Wijaya Komang Aman (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
Tatwa and susila are only understood by certain people. While the elements of the ceremony can be done by anyone, easy and practical to do as an implementation in connecting themselves with Ida Sang Hyang Widhi.At present with the progress of the era where the level of welfare of the peopleThe implementation of religious activities such as ceremonies went very well, more vibrant and smoothly, Likewise the holy places (Pura) are very beautiful and the development is well developed. Behind the very positive impact on current progress also leaves things that are less profitable. Advances in the era of recruiting efforts to search for material harder, full of competition. Excessive material demands often make people forget, increasingly enslaved by material labor, greedy, ambitious, indulging in all forms of desire. Spiritual awareness is covered by things that are temporary, such as forgetting the true purpose of life as a human. Finally, all of that must be redeemed with a long and physical suffering. This reflects the teachings of the religion he adheres to have not permeated the heart. . In order to build and ignite the fire of consciousness and wisdom is Balinese in the holy teachings of the Vedas, Understanding the true teachings of religion can humans breaking away from all worldly attachments, gradually a misleading form of desire to increase holiness to achieve moksa. Keywords: Samnyasa, Manawa Dharmasastra